2021
DOI: 10.1002/er.7129
|View full text |Cite
|
Sign up to set email alerts
|

Development of high performance and low‐cost solid oxide fuel cell stacks: Numerical optimization of flow channel geometry

Abstract: Summary Solid oxide fuel cell (SOFC) stacks with small volume and weight are essential to obtain higher specific and volumetric power densities as an alternative to conventional SOFC stacks with interconnectors having machined flow channels. This can be achieved by employing thin sheet interconnectors with flow channels formed by stamping methods rather than conventional machining of thick bulk materials. Besides the determination of process parameters providing defect free manufacturing of the desired channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 52 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…The only attribute that changed is the channel configuration. Instead of a straight parallel channel, a taper of 75° is given to the vertical edge of the channels making it a trapezoidal channel with a wider channel width of 1.5 mm and narrow rib width of 0.5 mm 27 . The taper angle of 75° is chosen from the work reported by R. M. Manglik and Y. N. Magar, 28 where triangular channel, a trapezoidal channel with internal inclination angles ( θ ) of 60° and 75°, and rectangular channel were studied and it was reported that (a) As θ increases, the heat transfer or Nusselt characteristics increases from θ = 45° to 90° with a significant change observed when θ changes from 60° to 75° for a trapezoidal channel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only attribute that changed is the channel configuration. Instead of a straight parallel channel, a taper of 75° is given to the vertical edge of the channels making it a trapezoidal channel with a wider channel width of 1.5 mm and narrow rib width of 0.5 mm 27 . The taper angle of 75° is chosen from the work reported by R. M. Manglik and Y. N. Magar, 28 where triangular channel, a trapezoidal channel with internal inclination angles ( θ ) of 60° and 75°, and rectangular channel were studied and it was reported that (a) As θ increases, the heat transfer or Nusselt characteristics increases from θ = 45° to 90° with a significant change observed when θ changes from 60° to 75° for a trapezoidal channel.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of a straight parallel channel, a taper of 75 is given to the vertical edge of the channels making it a trapezoidal channel with a wider channel width of 1.5 mm and narrow rib width of 0.5 mm. 27 The taper angle of 75 is chosen from the work reported by R. M. Manglik and Y. N. Magar, 28 where triangular channel, a trapezoidal channel with internal inclination angles (θ) of 60 and 75 , and rectangular channel were studied and it was reported that (a) As θ increases, the heat transfer or Nusselt characteristics increases from θ = 45 to 90 with a significant change observed when θ changes from 60 to 75 for a trapezoidal channel. (b) The ratio Nu/fRe which was used as a measure of the relative surface-area compactness or increased convective heat transfer surfacearea density showed a drastic increase for θ = 60 to 75 after which the change is almost linear with an increase in θ up to 90 .…”
Section: Geometrymentioning
confidence: 99%